Reasons for the Low Male Involvement in Routine Child Immunization in Hoima District Uganda using the Attitude, Social Influence and Self Efficacy Model - Charles, Baguma; Juliet, N. Babirye; Paul, Oryema; Peter, Wasswa; Lynn, Atuyambe (Journal of Immunization, 2016)
Millions of children continue to miss immunizations each year despite global increases in financing and advances in vaccine technology. Male involvement in routine child immunization activities could improve and sustain coverage but is rarely emphasized in immunization programs or research. This study identified factors associated with male involvement in routine child immunization using the attitude, social influence and self-efficacy model.A household cluster survey was conducted among 460 fathers aged 18 years or more, with children aged 10-23 months. A semi-structured interviewer-administered questionnaire was used to collect data. Prevalence Risk Ratios (PRRs) were used to measure associations with level of involvement using generalized linear models with Poisson family, log link and robust standard errors in STATA 12. Our findings show that half (51%, 236/460) of the respondents were aged 25-34 years; 36% (166/460) had completed eight or more years of formal education. Although90% (415/460) of the respondents were willing to be involved, only 29% (133/460) were highly involved in routine child immunization. Highly involved fathers had a positive attitude towards involvement in routine child immunization (adj. PRR 2.3, 95% CI 1.18 – 4.98) and were ≥45 years adjusted prevalence risk ratio (adj. PRR) 2.0, 95% confidence interval (CI) 1.15 - 3.76. Traders had a lower involvement compared to those engaged in other occupations (adj. PRR 0.55, 95% CI: 0.37 - 0.82). In conclusion, few fathers were involved in routine child immunization. Strategies to improve fathers’ positive attitude such as health education are needed to increase their involvement, specifically targeting younger fathers and traders.
Keywords: Male involvement in routine child immunization Hoima.